Acrothoracican barnacles (Lithoglyptida) in Taiwan, including the taxonomic status of Balanodytes taiwanus Utinomi, 1950 and cryptic diversity of Auritoglyptes bicornis (Aurivillius, 1892) - Chan, Benny K.k.; Cheang, Chi Chiu; Chen, I-Han; Kolbasov, Gregory A. (Zootaxa, 2013)
We list five acrothoracican barnacles of the order Lithoglyptida currently found in Taiwanese waters, including two new records, Trypetesa habei Utinomi, 1962 and Berndtia purpurea Utinomi, 1950 and a new undescribed species of the genus Lithoglyptes. We also investigate the morphology and molecular genetics of Balanodytes taiwanus Utinomi, from its type locality, Taiwan. The original description of B. taiwanus in Utinomi (1950a) reported the absence of caudal appendages. Re-examination of the somatic body of one of the syntype specimens (the other syntype only having an opercular bar remaining) of B. taiwanus deposited in the Seto Marine Laboratory in Japan, revealed the presence of caudal appendages. The morphology of our specimens collected in various locations in Taiwan fits the description in Utinomi (1950a) and all have caudal appendages. The diagnosis of Balanodytes Utinomi, 1950 is revised herein. The genus Armatoglyptes Kolbasov & Newman, 2005 is a nomen nudum and a junior synonym of Balanodytes. Our results also show that the widespread species Lithoglyptes habei Tomlinson, 1963 is a junior synonym of B. taiwanensis. The molecular sequence divergencse of the 16S RNA and COI genes were studied for samples of another monotypic genus Auritoglyptes (A. bicornis) from different regions of Taiwan. It was shown that there are at least three phylogenetic clades in Taiwan, suggesting that Auritoglyptes represents a cryptic species complex.